PENGARUH KUALITAS AUDITOR, KONDISI KEUANGAN PERUSAHAAN, OPINI AUDIT TAHUN SEBELUMNYA, PERTUMBUHAN PERUSAHAAN DAN DEBT DEFAULT TERHADAP KEMUNGKINAN PENERIMAAN OPINI AUDIT GOING CONCERN - Karyanti Karyanti; Suryo Pratolo (Journal of Accounting and Investment, 2009)
This research comprises an empirical study that is carried out to identify the influence of auditor quality, company financial condition, previous year audit opinions, company growth, and debt default toward the acceptance or going concern audit opinion.  The population of the research is the manufacture companies listed in Indonesian Stock Exchange in the year 2002-2006.  The number of the samples are 38 companies (in 5 year period).  The data collection method is purposive sampling.  The data used in this study are secondary data in the form of documentation data from Indonesian Capital Market Directory (ICMD).  Hypothesis testing is conducted by employing logistic regressions. The findings show that previous year audit opinions and debt default influence significantly toward the possibility of the acceptance of going concern audit opinion.  Meanwhile, the auditor quality, company financial condition and company growth do not influence the possibility of the acceptance of going concern audit opinion.